TRPC6 counteracts TRPC3-Nox2 protein complex leading to attenuation of hyperglycemia-induced heart failure in mice - Oda, Sayaka (2017)
Fil: Oda, Sayaka. National Institute for Physiological Sciences. Division of Cardiocirculatory Signaling; Japón